A Tale of Two Cities: An Experiment on Inequality and Preferences - Maria Bigoni; Stefania Bortolotti; Veronica Rattini (Institute of Labor Economics (IZA), 2018)
In an online experiment, we exploit the existing disparities in socio-economic status within an Italian city, to study how these differences correlate with preferences in strategic and non-strategic situations. Our findings indicate that participants living in an area characterized by a high socio-economic environment tend to trust more and are more inclined to reciprocate higher levels of trust, as compared to those coming from less wealthy neighborhoods. This behavioral difference is, at least in part, driven by heterogeneities in beliefs: subjects from the most affluent part of the city have more optimistic expectations on their counterpart's trustworthiness than those living in a lower socio-economic environment. By contrast, no significant differences emerge in other preferences: generosity, risk-attitudes, and time preferences. Finally, we do not find any systematic evidence of out-group discrimination based on neighborhood identity.
Keywords: C90; D31; D63; R23; 330; beliefs; discrimination; generosity; risk attitudes; time preferences; trust; trustworthiness